RESEARCH NON-LINEARY DEMAND FUNCTION AND EQUILIBRIUM INDICATORS OF SUPPLY CHAIN UNDER ІNFORMATION ASYMMETRY BY THE MEANS OF THE PACKAGE SYMBOLIC TRANSFORMATION MAPLE - Kobets В.М. (Journal of Information Technologies in Education (ITE), 2011)
In the paper is investigated the research issues of nonlinear economical indicators for market structures by means of the symbol transformation system Maple.